Frank Guilbert photo albums, - Guilbert, Frank W., d. 1940
Six photo albums of 8x10 black and white prints taken by Frank W. Guilbert primarily in the 1920s. Photographs are scenic views of lakes, roads, mountains and other scenic views around Spokane and the Inland Northwest. Many pictures of Mt. Spokane are included, as well as Liberty Lake, Loon Lake, Priest Lake. Pictures of Manito Park in Spokane and pictures of roads and trails are also present.